Profil Penguasaan Konsep Struktur Atom pada Siswa Kelas X MIPA SMA Negeri 4 Palangka Raya Tahun Ajaran 2018/2019 - Yulita Tasya; I Made Sadiana; Nopriawan Berkat Asi (FKIP Universitas Palangka Raya, 2020)
Atomic structure is one of the chemistry subject matter taught in high school / MA. This material was studied in class X SMA about the development of atomic theory, the basic particles making up atoms, electron configurations, and quantum numbers. This concept is the basic concept of chemistry to understand chemical bonds. This study aims to describe the profile of the mastery of the concept of Atomic Structure in class X high school students. This research is a type of descriptive study carried out in SMA Negeri 4 Palangka Raya with 30 research subjects as Grade X MIPA-1 students. The data used in this study were in the form of the chemistry teacher's lesson plan, the student's concept mastery data obtained through the description test, and student interview data. The results showed 1) an average of 62.16% were in the medium category. 2) Students can explain the development of atomic theory to show the advantages and disadvantages of each atomic theory with an average mastery of the concept of 68.75% with the medium category. 3) Students can determine the elementary particles (protons, electrons, and neutrons) of an atom based on atomic number and mass number with an average mastery of concepts of 61.47% in the medium category. 4) Students can classify elements into isotopes, isobars, and isotope with an average mastery of concepts of 88.88% with a high category. 5) Students can determine quantum numbers in the outermost electrons of an element or ion with an average mastery of concepts of 21.04% in the low category.